Islam And The Role Of Private Universities In Preventing Drug Abuse In The District Asahan - Abidin, Zainal; Daulay, Nurussakinah; Nasution, Zulkarnain (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This article aims to analyze the views of universities in preventing drug abuse, how university programs arrive at the solutions provided for preventing drug abuse on private campuses in Asahan. The type of research in this study uses qualitative research, namely research using data collection techniques without using numbers or other nominal fractions, because this requires data in the field. Then more research was collected and was in the form of information or information obtained based on informants. This research took place at private campuses/universities throughout Asahan Regency. Data collection techniques use interviews, field observations and documentation studies. Data processing and analysis techniques use data reduction, data presentation and drawing conclusions. The research time starts from the initial research on July 20 2023. The results of the research found that the view of university administrators regarding the prevention of drug abuse in Asahan Regency is the need for active participation and participation in carrying out activities to prevent narcotics abuse carried out in the campus environment, reporting all forms of possession, distribution or abuse of drugs that occur in the campus environment, actively in participating in training, seminars, workshops on preventing drug abuse both carried out by campus and outside campus, establishing good communication with peers and other campus residents (Rector, Dean, Lecturers, parents, and campus security officers), and What students can do to play a role in this industrial era and take steps and take a place as the driving force of this country is to develop critical thinking patterns and not be easily eroded by negative influences. Then the program uses three approaches, namely a communicative approach, an informative approach, and an educational approach.